A maximum rupture model for the central and southern Cascadia subduction zone—reassessing ages for coastal evidence of megathrust earthquakes and tsunamis - Nelson, Alan R. (2022)
A new history of great earthquakes (and their tsunamis) for the central and southern Cascadia subduction zone shows more frequent (17 in the past 6700 yr) megathrust ruptures than previous coastal chronologies. The history is based on along-strike correlations of Bayesian age models derived from evaluation of 554 radiocarbon ages that date earthquake evidence at 14 coastal sites. We reconstruct a history that accounts for all dated stratigraphic evidence with the fewest possible ruptures by evaluating the sequence of age models for earthquake or tsunami contacts at each site, comparing the degree of temporal overlap of correlated site age models, considering evidence for closely spaced earthquakes at four sites, and hypothesizing only maximum-length megathrust ruptures. For the past 6700 yr, recurrence for all earthquakes is 370–420 yr. But correlations suggest that ruptures at ∼1.5 ka and ∼1.1 ka were of limited extent (<400 km). If so, post-3-ka recurrence for ruptures extending throughout central and southern Cascadia is 510–540 yr. But the range in the times between earthquakes is large: two instances may be ∼50 yr, whereas the longest are ∼550 and ∼850 yr. The closely spaced ruptures about 1.6 ka may illustrate a pattern common at subduction zones of a long gap ending with a great earthquake rupturing much of the subduction zone, shortly followed by a rupture of more limited extent. The ruptures of limited extent support the continued inclusion of magnitude-8 earthquakes, with longer ruptures near magnitude 9, in assessments of seismic hazard in the region.